6.2: Flexible Display Driven by Solution‐Processed OTFTs Manufactured Using All‐Sputtered Electrodes. Issue 1 (1st July 2013) - Lee, Jung Eun; Kim, Kyung Min; Na, Hyung II; Park, Chang Bum; Yoo, Soon Sung; Yang, Myoung Su; Kang, In Byeong; Yeo, Sang Deog
Abstract: We have developed a 3.5‐inch flexible display driven by solution‐processed organic thin‐film transistors manufactured using all‐sputtered electrodes. For large area and mass production of OTFTs, low‐cost and low‐resistance copper electrode is adopted for S/D and Gate electrodes. There is no significant degradation after delamination of plastic substrate from the glass and bending stress.